Populasi dan Spesies Serangga Hama di Gudang dengan Penciri Struktur Bangunan dan Asal Komoditasnya yang Beragam di Tiga Pasar Lokal pada Kecamatan Ilir Timur II dan Kalidoni, Kota Palembang Sumatera Selatan - Cindi, Aulia; Herlinda, Siti; Yulistin, Eka; Setyawati, Anita; Anggraini, Erise; Padila, Padila; Dwitami, Egga; Ardellta, Nasya; Humairoh, Balqis; Maharani, Shara (Seminar Nasional Lahan Suboptimal, 2024)
Cindi, A, Herlinda, S., Yulistin, E., Setyawati, A., Anggraini, E., Padila, P., Dwitami, E., Ardellta, N., Humairoh, B., Maharani, S. (2024). Populations and storage pest species from three local market with various building structures and commodity origins in sub-district of Ilir Timur II and Kalidoni, Palembang South Sumatera. In Herlinda S. 2024. Proseding Seminar Nasional Lahan Subtropis ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 244‒254). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Storage pest insects damage stored materials quantitatively and qualitatively. Quantitative damage includes damage to stored materials which decrease in quality, damage by the Sitophilus oryzae species reaches 10-30% in Storages. The research aimed to identify and analyze the pest insect populations attacking stored commodities and to determine the influence of building structures on the diversity of species and populations of warehouse pests attacking in the markets of Ilir Timur II and Kalidoni sub-districts. The research was conducted by surveying markets in the Sub-Districts of Ilir Timur II and Kalidoni to observe the morphology of storage pest species. The study found that different markets have different storage conditions and populations of storage pests. Based on the identification of Storage pest insects found in traditional markets, 7 species of Storage pest insects were found, namely Sitophilus oryzae, Tribollium castaneum, Callosobrucus chinensis, Rhizoperta dominica, Cryptolestes ferrugeneus, Oryzaephilus surinamensis and Carpophilus dimidiatus. In Ilir Timur II District, at the 1st and 2nd markets, 5 species of Storage pest insects were found each, while at the market in Kalidoni District, 4 species of Storage pest insects were found. The commodities attacked were peanuts, green beans, rice and flour. Each market has a different treatment for commodity storage building structures such as ventilation, pallets, types of sacks, doors and floors.